PHYSICOCHEMICAL PROPERTIES OF HERBAL SOAP MADE FROM AVERRHOA BILIMBI LEAF AND FLOS LONICERAE - HJ ZAITON, SITI NURUL ’AIN; AZMAN, HAIRUL AMIZA; HAMBALI, NORHAFINI; ONN, MUNIRAH; MOHAMAD, SAIFUL NAJMEE; MUSTAFA, MOHD HAIKAL (Malaysian Journal of Science, 2024)
Malaysian herbs, Averrhoa Bilimbi, and Flos Lonicerae, are widely known in traditional Chinese medicine. Both are used as natural remedies for jaundice treatment in newborns. Formulating herbal bath soap by the saponification method is proposed because newborn babies are poor feeders. Today, a lot of chemicals are used in soap production. Users will have a wide range of issues due to chemicals like parabens and triclosan. As a result, soap is made from herbs without chemicals. This herbal soap uses two herbs, Averrhoa Bilimbi leaf and Flos Lonicerae. Paper journals examining these herbs’ physicochemical properties are scarce in Malaysia. After the herbal soap has been successfully created, it will be examined for its physicochemical properties. The antioxidant activity and total phenolic content (TPC), of Averrhoa Bilimbi leaf extract and Flos Lonicerae extract were all tested. The antibacterial activity, heavy metal and pH tests were also validated the suitability of this herbal soap for skin application. According to the findings, Averrhoa Bilimbi leaf extract had a TPC value of 24.49 mg GAE/g compared to 4.96 mg GAE/g for Flos Lonicerae extract. Averrhoa Bilimbi leaf required a slightly higher concentration of 0.0588 g/mL extract to inhibit 50% of the DPPH assay compared to Flos Lonicerae plant extract, which required 0.0315 g/mL. Since there was no evidence of any bacterial growth, the herbal soap was effective against all the tested bacterial strains. The heavy metal test showed the soap does not contain any lead, mercury or arsenic and exhibits a pH value which close to the range for suitable skin application.